PENGARUH PELATIHAN KERJA, DISIPLIN KERJA DAN MOTIVASI TERHADAP KINERJA PADA PT. DUA MITRA LANGGENG SURAKARTA - Wahyu Winarno (STIE AUB Surakarta, 2018)
The purpose of this study is to determine the effect of job training, work discipline and motivation on employee performance PT. Dua Mitra Langgeng Surakarta. Population in this research all employees of PT. Two partners Langgeng numbered 250 people, while the sample used as many as 100 people who become respondents and sampling techniques of this study using accidental sampling technique. Based on the results analysis known to job training, work discipline and motivation have an effect on signifikan to employee performance of PT. Dua Mitra Langgeng Surakarta. The simultaneous test results of job training variables, work discipline and motivation have a significant effect on employee performance variable of PT. Dua Mitra Langgeng Surakarta.Keywords: Job Training, Work Discipline, Motivation and Performance